The perspective of Muslim employees towards motivation and career success - Sulaiman, Mohammed; Mohd. Israil, Khaliq Ahmad; Baraa , Sbaih; Mohd. Israil, Khaliq Ahmad (Faculty of Social Sciences and Humanities, UKM, 2014)
Understanding Muslims employees’ perspective of motivation and career success is an important factor towards achieving organizational success. The present research attempts to investigate motivation and career success from Islamic perspective. Employing a qualitative research approach, in-depth interviews were carried out on a total sample of 7 respondents; 6 males and 1 female. The respondents hold senior managerial positions in their organizations which include the banking, government, manufacturing and automobile sectors. The research led to some findings; that Muslim employees are more interested in intrinsic motivational factors coupled with a fair balance in worldly living to achieve career success; that respondents are aware of Maqasid Al-shariah and consider their roles in the worldly life as a test for their akhirat; that respondents are more concerned towards seeking the pleasure of Allah and good abode in the hereafter.